PEMBERDAYAAN UMKM MELALUI IMPLEMENTASI MANAJEMEN USAHA DAN PEMASARAN BERBASIS MEDIA SOSIAL BAGI PELAKU USAHA UMKM DI KECAMATAN ABELI - Windayani Windayani; Sri Wiyati Mahrani; Triwulandari Nehru Putri; Ghalib Suprianto; Muhammad Sabrian Oehoedoe (Yayasan Nusa Cendekia Global, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in strengthening the local economy. However, MSME actors in Abeli District still face various challenges, particularly in business management and the utilization of social media as a marketing tool. This Community Service activity aimed to empower MSME actors through the implementation of business management and social media–based marketing to enhance product competitiveness. The program involved 25 MSME participants and was conducted using socialization, training, mentoring, and evaluation methods. The training materials covered business management, simple financial record-keeping, digital marketing strategies, and product branding enhancement. The results of the program indicated an improvement in participants’ understanding of business management and the use of social media as a promotional medium. Participants began to apply simple financial recording practices, create business social media accounts, and develop promotional product content. This program had a positive impact on strengthening MSME capacity and opening opportunities for market expansion. Therefore, empowering MSMEs through business management and social media–based marketing has proven effective in improving business performance and enhancing the competitiveness of local products in Abeli District.